2014
DOI: 10.1186/1756-0500-7-597
|View full text |Cite
|
Sign up to set email alerts
|

First report on the molecular epidemiology of Malaysian Staphylococcus epidermidis isolated from a University Teaching Hospital

Abstract: BackgroundStaphylococcus epidermidis is a pathogen associated with nosocomial infections whose medical importance has increased due to progressively invasive medical procedures. In this study, we characterized the molecular epidemiology of S. epidermidis strains circulating in our university hospital situated in Kuala Lumpur, Malaysia.FindingsA total of 798 S. epidermidis were isolated from our university hospital, where 56.3% of the isolates were found to be cefoxitin (methicillin) resistant and also positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Such as was observed in our results, a large genetic variability in PFGE analysis of healthcare associated S. epidermidis has been reported in many studies (Nunes et al, 2005;Cherifi et al, 2013;Sani et al, 2014). In spite of the diversity observed in the PFGE analysis, multilocus sequence typing (MLST) studies of these isolates showed that the prevalent PFGE types generally belonged to few sequence types (ST) of clonal complex 2 (CC2); among them, ST2 and ST23 in Brazil (Iorio et al, 2012), ST2 and ST54 in Belgium (Cherifi et al, 2014) and ST2 in China (Li et al, 2009;Du et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Such as was observed in our results, a large genetic variability in PFGE analysis of healthcare associated S. epidermidis has been reported in many studies (Nunes et al, 2005;Cherifi et al, 2013;Sani et al, 2014). In spite of the diversity observed in the PFGE analysis, multilocus sequence typing (MLST) studies of these isolates showed that the prevalent PFGE types generally belonged to few sequence types (ST) of clonal complex 2 (CC2); among them, ST2 and ST23 in Brazil (Iorio et al, 2012), ST2 and ST54 in Belgium (Cherifi et al, 2014) and ST2 in China (Li et al, 2009;Du et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…These findings questions on the eligibility of these antibiotics to be used in the treatment of S. epidermidis infections. Pattern of resistance of S. epidermidis against cefoxitin, erythromycin and gentamicin were generally similar to a study conducted in a teaching hospital in Malaysia in 2014 [54]. This resistance frequencies is also in agreement with reports that this bacterium are commonly resistant to group of antibiotics like penicillins, macrolides and aminoglycosides [2,12,15] None of the clinical S. epidermidis isolates were found to be resistant against linezolid.…”
Section: Antibiotic Resistance Patterns Of the S Epidermidis Isolatessupporting
confidence: 89%
“…49,50 In regards to the distribution of SCCmec types, similar outcome was found between this study and Garza-Gonzalez et al, 51 whereby the most detected SCCmec type was IVa. Mert et al, 52 had reported that generally, majority of MR-CoNS isolated from blood harboured SCCmec type IV (n=65, 24.9%) while Sani et al, 53 found that type IV as the most common (42%) in clinical samples. In contrast, type III was observed as the most commonly distributed in Brazil in which more than 50% were isolated from blood cultures from 1990 to 2009.…”
Section: Discussionmentioning
confidence: 99%